Colloid transport in saturated porous media: Elimination of attachment efficiency in a new colloid transport model. Issue 5 (30th May 2013) - Landkamer, Lee L.; Harvey, Ronald W.; Scheibe, Timothy D.; Ryan, Joseph N.
Key Points: This colloid transport model eliminates the empirical attachment efficiency. Introduce a new paradigm for colloid re‐entrainment behavior. Model parameters related to magnitude of secondary energy minimum Abstract : [1] A colloid transport model is introduced that is conceptually simple yet captures the essential features of colloid transport and retention in saturated porous media when colloid retention is dominated by the secondary minimum because an electrostatic barrier inhibits substantial deposition in the primary minimum. This model is based on conventional colloid filtration theory (CFT) but eliminates the empirical concept of attachment efficiency. The colloid deposition rate is computed directly from CFT by assuming all predicted interceptions of colloids by collectors result in at least temporary deposition in the secondary minimum. Also, a new paradigm for colloid re‐entrainment based on colloid population heterogeneity is introduced. To accomplish this, the initial colloid population is divided into two fractions. One fraction, by virtue of physiochemical characteristics (e.g., size and charge), will always be re‐entrained after capture in a secondary minimum. The remaining fraction of colloids, again as a result of physiochemical characteristics, will be retained "irreversibly" when captured by a secondary minimum. Assuming the dispersion coefficient can be estimated from tracer behavior, this model has only two fitting parameters: (1) the fraction of the initial colloid population that will be retained "irreversibly" upon interception by a secondary minimum, and (2) the rate at which reversibly retained colloids leave the secondary minimum. These two parameters were correlated to the depth of the Derjaguin‐Landau‐Verwey‐Overbeek (DLVO) secondary energy minimum and pore‐water velocity, two physical forces that influence colloid transport. Given this correlation, the model serves as a heuristic tool for exploring the influence of physical parameters such as surface potential and fluid velocity on colloid transport.